THE ROLE OF SHARIA SAVINGS AND LOANS AND FINANCING COOPERATIVES (KSPPS) IN COMMUNITY ECONOMIC EMPOWERMENT (STUDY AT KSPPS BMT ALFA DIRHAM MANDIRI CIREBON) - Hendrawan, Yadi; Mochamad Surya, Candra; Ziyadatun Nasiah, Riska (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Sharia Savings and Loans and Financing Cooperative (KSPPS) BMT Alfa Dirham Mandiri Cirebon has been active since 2014 with the main aim of encouraging community economic growth by providing easy and fair access to financing. However, KSPPS has not been fully accepted as the main choice by the community. This research aims to identify the role of KSPPS in community economic empowerment and analyze the factors that support and hinder KSPPS' efforts to improve community welfare. This research is field research with a qualitative descriptive approach. Data was obtained through interviews with KSPPS employees and documentation that recorded the history, organizational structure, and illustrations of KSPPS financing. The research results show that KSPPS has carried out its role in accordance with sharia principles, by actively providing access to financing, education, training, and implementing social programs for the development of local communities, including infrastructure development and social assistance. Supporting factors that make KSPPS the community's first choice include sharia principles in operations, security, trust, justice, flexible financing, personal service, education, training, fair profit sharing, and social activities. However, there are also inhibiting factors such as lack of education and outreach, competition with other financial institutions, limited capital and technology, unprofessional management, lack of product innovation, and low public trust.